Agency Agreement on Bancassurance Activities in the Perspective of Business Competition Law - Windha Windha; Syarifah Lisa Andriati (International Journal of Artificial Intelligence Research, 2022)
One form of insurance product marketing activity that has undergone significant development is known as bancassurance. The bancassurance business model consists of referral activities, distribution activities, and product integration activities, which as a whole are a form of agency agreement between insurance companies as principals and banks as insurance agents. However, the KPPU has a different interpretation of bancassurance activities. The KPPU considers bancassurance activities as tying agreements rather than agency agreements. This journal research is a normative legal study using secondary data. All materials that were successfully collected will be analyzed using descriptive analysis. The results of this journal research are that bancassurance is an agency agreement in the narrow sense that is excluded in Act Number 5 Year 1999, and from the perspective of the KPPU as a competition law enforcer, bancassurance activities are not activities based on agency agreements in the narrow sense as intended in Article 50 letter d and therefore are excluded by Act Number 5 Year 1999, but the KPPU views bancassurance activities as tying agreements.